Genetic analysis of erythrocyte potassium concentration in cattle - Caminhas, Maria Margareth Theodoro; Bortolozi, Jehud; Chamma, Oslei José; Kohayagawa, Aguemi (Pesquisa Agropecuaria Brasileira, 1992)
Red-cell potassium concentration was determined in five breeds of cattle: Brown Swiss, Nelore, Pitangueiras, Gir and Girolanda. All the cattle examined for the red-cell potassium concentration presented low potassium concentration or LK type. This were divided in the following sub-types: low-low potassium concentration (LLK variation: 7.0 -15.9 m-equiv/l) in 16.9% of the animals; medium-low potassium concentration (MLK variation: 16.0 - 30.9 m-equiv/l) in 77% of animals and high-low potassium concentration (HLK variation: 31.0 - 50.0 m-equiv/l) in 6.1% of the animals. This results may be associated with a tropical environment because animals with red-cell potassium concentration have advantage in this environment.
Keywords: red-cell potassium concentration; Brown Swiss; Nelore; Pitangueiras; Gir; Girolanda